TRANSFORMASI PEMBELAJARAN VOKASI MELALUI PELATIHAN 3D PRINTING SEBAGAI UPAYA PENINGKATAN KETERAMPILAN TEKNIS DI SMK NEGERI 1 KRAGILAN - Abdillah, Hamid; Fawaid, Moh; Ardiansyah, Atih (Jurnal Abdi Insani, 2025)
The development of manufacturing technology requires vocational schools toadapt to industrial changes. One rapidly developing technology is 3D printing,which can produce prototypes quickly, precisely, and at a relatively affordablecost. SMK Negeri 1 Kragilan, as a school located in the Serang industrial area,strives to optimize the Teaching Factory through the integration of thistechnology. This community service activity is carried out in the form of 3Dprinting training for teachers and students, with the aim of improving technicalcompetency while supporting the transformation of vocational learning. Thetraining method is participatory with a hands-on approach, including anintroduction to design software, 3D printer operation, and the creation ofsimple products. Evaluation is carried out through a Likert-scale questionnaire,product documentation, and participant testimonials. The training resultsshowed significant improvements in aspects of material understanding(average 4.3), technical skills after training (4.4), and benefits for work (4.7).Participants successfully produced five product prototypes, including souvenirs,mobile phone casings, miniature buildings, gear models, and key chains.Participant testimonials confirm that the training is beneficial, although there isstill input regarding the need for more practice time. This activity confirmedthat 3D printing training not only improves the technical skills of teachers andstudents but also opens up opportunities for product innovation within theTeaching Factory environment. These results provide a starting point fordeveloping digital technology-based creative entrepreneurship in vocationalschools.